An installation for the investigation of radiation and thermal gas liberation from inorganic materials; Russian journal of non-ferrous metals; Vol. 52, N 1 - Nikitenkov N. N. Nikolai Nikolaevich; Khashkhash A. M.; Shulepov I. A.; Khoruzhii V. D.; Tyurin Yu. I. Yuri Ivanovich; Chernov I. P. Ivan Petrovich; Kudryavtseva E. N. (2011, 2011)
A high-vacuum installation for the qualitative and quantitative investigation of the content of monatomic and molecular gases (hydrogen, oxygen, nitrogen, water vapors, gaseous hydrocarbons, CO2, CO, etc.) on the surface and in the near-surface layers of compact and porous materials is designed. Methods of radiation-stimulated and thermally stimulated desorption, as well as a technological method for degassing solid materials via electron irradiation, are achieved in the installation. The results of an investigation into the hydrogen content upon saturation and its emission from polycrystalline (average grain size d > 1μm) and submicrocrystalline (d < 0.1 μm) titanium under radiation and thermal effects are presented as an example of the use of the abovementioned methods.